Ketofol performance to reduce postoperative emergence agitation in children undergoing adenotonsillectomy. Issue 1 (1st January 2020) - Ali, Idress; Alahdal, Murad; Xia, Haifa; S. El. Moughrabi, Arafa; Shiqian, Huang; Yao, Shanglong
ABSTRACT: Background : Emergence agitation is a reformed state of mindfulness, which starts with a sudden form of anesthesia and progresses through the early repossession age. Thus, the purpose of this study is to evaluate 1:3 ketofol performance on children 3–15 years old undergoing adenotonsillectomy.Methods : A total of 60 children aged 3–15 years undergoing adenotonsillectomy were randomly allocated to receive low-dose ketamine 0.15 mg/kg followed by propofol 0.45 mg/kg i.v. ketofol (1:3) about 10 min before the end of surgery in comparison to 60 children aged 3–15 years who received only normal saline and dextrose. Anesthesia was induced and maintained with sevoflurane. Postoperative pain and EA were assessed with objective pain score (OPS) and the Pediatric Anesthesia Emergence Delirium (PAED) scale, respectively. EA was defined as a PAED 10 points. Recovery profile and postoperative complications were also recorded.Results : The incidence and severity of EA were found significantly lower in the ketofol group in comparison to the control group with a percentage of (13.33% vs 48.33%) (8% vs 15%) respectively (P < 0.05). Also, the time for interaction from anesthetic tainted to extubating in the ketofol set was significantly less than in the control group (P < 0.05). Interestingly, there are no opposing events such as nausea, laryngospasm, bronchospasm, hypotension, bradycardia, bleeding, or postoperative respiratory depression (respiratory rate: <16) were noticed in the ketofol supervision (P > 0.05). Moreover, the heart rate was meaningfully higher in the control group starting at the time of tracheal extubating in comparison to the children undergone ketofol (P < 0.05). Alert score and time from painkilling tainted till liberation from PACU showed substantial significant changes at ketofol set (P < 0.05).Conclusion : Ketofol (1:3) shows significant performance to reduce postoperative agitation in the children undergone adenotonsillectomy.